Evaluation of Some Popular Rice Varieties of Bangladesh for Physical and Cooking Quality Properties - Md Abdul Wahed Khan; Mahbuba Sultana Priti; Md Sohel Rana; Md Nuruzzaman; Muhammad Javidul Haque Bhuiyan; Sharif Ar Raffi (Research in Agriculture Livestock and Fisheries, 2024)
Rice is the primary staple meal in many parts of the world. Therefore, both consumers and producers must pay close attention to the physical and cooking characteristics of grains. The present study was conducted to evaluate the physical and cooking quality characters in twenty popular Bangladeshi boro rice genotypes along with one japonica rice genotype. A high degree of significant variation was observed for all the characters studied. Genotypes BRRI dhan55, BR16, BRRI dhan57, BINA dhan-6 and BINA dhan-14 has the maximum length of grain before cooking (L1). BRRI dhan36, BRRI dhan57, BRRI dhan55 and BINA dhan-6 were the best performer in terms of grain length after cooking (L2). BRRI dhan57 and BRRI hybrid dhan1 were best for width of grain before cooking (W1). BRRI dhan57, BRRI dhan29 and BRRI dhan36 were exhibited minimum width of grain after cooking (W2). Yukihikari, BRRI hybrid dhan3 and BRRI dhan36 were best for grain elongation ratio. Highest grain length/width ratio before cooking (L1/W1) was observed in genotype BRRI dhan57, BRRI hybrid dhan1 and BINA dhan-14. The highest grain length/width ratio after cooking (L2/W2) was recorded in genotype BRRI dhan57 and BRRI dhan36. Best genotype for percent water uptake (WU %) after cooking was BRRI dhan28 (180%). The best genotypes for solid in cooking water (SCW) were BRRI dhan36 (0.897%), BRRI dhan28 (0.956%), Yukihikari (1.043%) and BRRI dhan29 (1.048%), respectively. The prominent performer genotypes for CT were BRRI dhan58 (18.38 minutes) followed by BR 14 (19.12 minutes), BRRI dhan28 (20.00 minutes) and BRRI dhan57 (19.82 minutes). Best genotypes for amylase content (AC) BRRI dhan28 (24.93%), BRRI dhan55 (24.91%), BRRI dhan59 (24.90%). Most of the rice genotypes had found low cooking time (GT) except BRRI dhan57, BRRI dhan59, Yukihikari which shows intermediate gelatinization temperature (GT). The comparative information about physical and cooking qualities of rice might be used as reference to develop high grain quality rice cultivars in future. Res. Agric. Livest. Fish. Vol. 11, No. 1, April 2024: 35-45